4, 4′-methylene diphenyl diisocyanate – Conformational space, normal vibrations and infrared spectra. (2nd September 2016) - Fug, Frank; Rohe, Kevin; Vargas, Jorge; Nies, Christophe; Springborg, Michael; Possart, Wulff
Abstract: Though 4, 4′-methylene diphenyl diisocyanate (4, 4′-MDI) is a key monomer in polyurethane synthesis, its infrared spectrum has not been discovered and assigned to the molecular vibrations in detail yet. To close that impedimental analytical gap, the conformers of 4, 4′-MDI and their vibrational properties are explored by DFT calculations and accurate IR band assignment is achieved for the first time by detailed comparison with measured spectra. Eight conformers are identified for 4, 4′-MDI. They can be separated into three classes with distinct physical and/or chemical properties. The classes differ in energy of the molecule and in the orientation of the isocyanate groups. For comparison with the IR spectrum measured for gaseous 4, 4′-MDI, the conformer spectra are broadened with Lorentzians, weighted according to the Boltzmann distribution for the conformer states, and added. This cumulated 4, 4′-MDI spectrum does not possess conformation-sensitive bands and differs significantly from the gas phase IR spectrum: IR bands are not related to the normal vibrations on a one-to-one basis since more than one normal mode contributes to each IR band. The IR normal modes show for all conformers that nearly all atoms are involved in each vibration. Moreover, spectra comparison reveals various significant differences that indicate that intermolecular interactions affect the measured spectra for the liquid and the gas state as well. Graphical abstract: Highlights: 4, 4′-MDI conformations identified by quantum-mechanical simulation. First time detailed vibrational analysis and IR band assignment for all conformers. All IR measured bands comprise several normal vibrations. Superposed conformer spectrum points to molecular interactions in liquid and gas.